GE_GERICHTE C/22779/2013 vom 15. Januar 2014 - GE Cour de justice (2014)
MESURE PROVISIONNELLE; PROTECTION DES MARQUES; CONCURRENCE DÉLOYALE; RISQUE DE CONFUSION | CPC.261; LPM.3.1; LPM.13.1; LCD.3.1.D;